Comorbid Factors and Duration of Illness in Dengue Hemorrhagic Fever Patients at Universitas Airlangga Hospital, Surabaya, Indonesia - Savita, Lady; Sulistiawati; Bramantono; Maimunah, Ummi (Journal of Community Medicine and Public Health Research, 2024)
Dengue hemorrhagic fever (DHF) continues to prevail in Indonesia annually. Individuals afflicted with dengue hemorrhagic fever may exhibit distinct clinical manifestations, and these can vary based on individual factors. Numerous elements can contribute to this diversity. Typically, adult patients with comorbidities face a less favorable prognosis for the primary disease. This study aimed to examine the impact of comorbid factors on the severity of DHF, as well as its duration. The comorbidities considered in this research encompassed hypertension, diabetes mellitus, and obesity. This research employed an analytical approach and was conducted at Universitas Airlangga Hospital from January to December 2022. Medical records served as the primary data source for this study. A total of 121 patient samples were collected based on specific criteria. The criteria included adults (>18 years) treated at Universitas Airlangga Hospital, who had no comorbid diseases other than those under study, and possessed complete medical record data. The sampling technique employed in this research was total sampling, which adhered to the inclusion and exclusion criteria. This research demonstrated that comorbid factors were not associated with the severity of DHF (p<0.05), while the duration of illness in DHF patients was correlated with the severity of the disease (p=0.027).